A hybrid system using Brayton cycle to harvest the waste heat from a direct carbon solid oxide fuel cell. (September 2019) - Yang, Zhimin; Zhang, Houcheng; Ni, Meng; Lin, Bihong
Highlights: A new DC-SOFC/Brayton cycle combined system is proposed. Performances of the proposed system and the sole DC-SOFC are compared. Brayton cycles are effective to recover the waste heat from DC-SOFCs. Influences of key parameters on the proposed system performance are revealed. Maximum power densities of DC-SOFC-based combined systems are compared. Abstract: A new hybrid system model is developed to evaluate the potentials of a Brayton cycle heat engine for waste heat recovery from a direct carbon solid oxide fuel cell (DC-SOFC). The maximum power density of the proposed system is up to 0.8675 W cm −2, which is approximately 1.8 times as large as that of the single DC-SOFC. Numerical calculations also indicate that the proposed hybrid system is an efficient approach to boost the fuel utilization, and the maximum power density of the proposed system is markedly better than that of the DC-SOFC/thermophotovoltaic cell, DC-SOFC/thermionic generator, and DC-SOFC/Otto heat engine hybrid systems except for the DC-SOFC/Stirling engine hybrid system. The optimum regions for power density, efficiency and operating current density of the proposed system are determined. The higher operating temperature and lower gap between the anode and carbon layer increase the power density and efficiency of the proposed system. Moreover, the higher heat transfer coefficient boosts the power density and efficiency at high current density. The compression efficiency, expansion efficiency and recuperator coefficient significantly affect the power density and efficiency.